PENGARUH PEMBERIAN NPK JAGO TANI TERHADAP PERTUMBUHAN DAN HASIL KEDELAI (Glycine max L. Merill) - Sundari; Karno; Arif Mukmin Hidayatullah (Jurnal Magrobis, 2022)
This study aimed to examine the effect of Jago Tani's NPK on the growth and yield of soybeans (Glycine max (L) Merill). This research started from August 2020 to November 2020 at Rempanga Village, Loa Kulu District, Kutai Kartanegara Regency. This study was arranged in a randomized block design (RAK) with three replications. The treatment level of Jago Tani NPK administration consisted of 7 levels, namely j0 (without urine/control), j1 (giving NPK 2 ml/liter), j2 (giving NPK 4 ml/liter of water), j3 (giving NPK 6 ml/liter), j4 (administration of NPK 8 ml/liter), j5 (administration of NPK 10 ml/liter) and j6 (administration of NPK 12 ml/liter) The results of the Jago Tani NPK study had no significant effect on the parameters of plant height, age of flowering plants, number of pods per plant, dry seed weight per plot, weight of 100 seeds (g) and yield per hectare (t ha-1). The average yield per hectare (t ha-1), the highest was obtained from treatment j3 (6 ml/liter) with a yield of 2,7797 t ha-1, while the lowest was from treatment j5 (10 ml/liter) with a yield of 2,0760 t ha-1.